Comparative audit of oxygen use in the prehospital setting in acute COPD exacerbation over 5 years. Issue 3 (15th November 2013) - Pilcher, Janine; Cameron, Laird; Braithwaite, Irene; Bowles, Darren; Swain, Andrew; Bailey, Mark; Weatherall, Mark; Beasley, Richard; Perrin, Kyle
Abstract : Background: In 2009 the Wellington Free Ambulance implemented an education programme to reduce high concentration oxygen delivery to patients with an acute exacerbation of chronic obstructive pulmonary disease (AECOPD). The aim of this audit was to compare pre-hospital oxygen delivery to patients with AECOPD before and after the programme. Methods: An audit of patients who presented to Wellington Regional Hospital by ambulance with an AECOPD in 2005 and then in 2010, after implementation of the education programme. Oxygen therapy was categorised as: HIGH, supplemental high concentration oxygen therapy ≥3 L/min and/or delivery via high concentration mask; NEB, high concentration oxygen only during nebuliser use; or LOW, neither of these. Results: In 2005 those in the HIGH, NEB and LOW categories were 81 (75.0%), 18 (16.7%) and 9 (8.3%) of 108 identified patients. In 2010 those in the HIGH, NEB and LOW categories were 80 (44.0%), 61 (33.5%) and 41 (22.5%) of 182 identified patients. The proportions of patients in the three oxygen groups were significantly different between 2005 and 2010 (p<0.001). Conclusions: The proportion of patients administered supplemental high concentration oxygen therapy markedly decreased between 2005 and 2010 following implementation of the education programme. However, in 2010 more than half of the patients not managed with high concentration oxygen therapy were still exposed to high concentration oxygen through the use of oxygen-driven nebulisers. To reduce exposure to high concentration oxygen in AECOPD the use of air-driven nebulisers or metered dose inhalers with spacers is required.